Affinity maturation of a t‐cell receptor‐like antibody specific for a cytomegalovirus pp65‐derived peptide presented by hla‐a*02:01 - Lee, Se Young; Ko, Deok Han; Son, Min Jeong; Kim, Jeong Ah; Jung, Keunok; Kim, Yong Sung (International Journal of Molecular Sciences, 2021)
Human cytomegalovirus (CMV) infection is widespread among adults (60–90%) and is usually undetected in healthy individuals without symptoms but can cause severe diseases in im-munocompromised hosts. T‐cell receptor (TCR)‐like antibodies (Abs), which recognize complex antigens (peptide–MHC complex, pMHC) composed of MHC molecules with embedded short peptides derived from intracellular proteins, including pathogenic viral proteins, can serve as diagnos-tic and/or therapeutic agents. In this study, we aimed to engineer a TCR‐like Ab specific for pMHC comprising a CMV pp65 protein‐derived peptide (495 NLVPMVATV503; hereafter, CMVpp65495‐503) in complex with MHC‐I molecule human leukocyte antigen (HLA)‐A*02:01 (CMVpp65495‐503/HLA‐ A*02:01) to increase affinity by sequential mutagenesis of complementarity‐determining regions using yeast surface display technology. Compared with the parental Ab, the final generated Ab (C1‐ 17) showed ~67‐fold enhanced binding affinity (KD ≈ 5.2 nM) for the soluble pMHC, thereby detecting the cell surface‐displayed CMVpp65495‐503/HLA‐A*02:01 complex with high sensitivity and exquisite specificity. Thus, the new high‐affinity TCR‐like Ab may be used for the detection and treatment of CMV infection.
Keywords: Antibodies; Antibody Affinity; Cell Line; Cytomegalovirus; Cytomegalovirus Infections; HLA-A Antigens; Humans; Peptides; Receptors, Antigen, T-Cell; Viral Matrix Proteins; Affinity maturation; Cytomegalovirus; Peptide/major histocompatibility complex class I complex; T‐cell‐re-ceptor‐like antibody; Yeast surface display